Design and Construction of an Agricultural Waste-Shredding Machine - Abdulkadir, S. A.; Dodo, S. M.; Jahun, B.G.; Malgwi, G. S.; Vanke, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Waste generation has become a major concern to the government, environmental regulatory bodies, and the society, especially with the current population pressure as well as the economic and social factors in Nigeria. This study was focused on design, construction, and performance evaluation of an Agricultural Waste-Shredder using locally available materials. The selected materials used to fabricate the machine were Metal sheet, Angle iron bars, Pulleys, belt, shaft, and Prime mover. The shredder has the feeding unit, the shredding unit, power transmission unit and the machine frame. The performance of the machine evaluated with beans stalk, the performance indices investigated were shredding efficiency and throughput capacity. Response surface methodology (RSM) was used to Maximize the efficiency of the machine at operational Speeds of 360rpm, 650rpm, and 975rpm with sieve apertures of 20mm, 30mm, and 40mm respectively. Maximum shredding efficiency of 93% was obtained when the shred aperture was 20mm at shredding speed of 975rpm. The maximum throughput capacity was 6.10kg kg/m at speed 975rpm and a minimum value of 5.14kg/m at 325rpm respectively. A quadratic model for shredding efficiency explained 94.78% of the variation in shredding efficiency. R2 (pred) of 70.42% suggests that the model is fit. The machine is easy to use and with a low cost of production to small and medium scale entrepreneurs in agriculture.